Public speaking training to improve the rhetorical skills of prospective trainers - Lusi Komala Sari (Universitas Pendidikan Indonesia, 2024)
The importance of public speaking in education is something that needs to be considered in the world of education in Indonesia, especially for prospective trainers in the Kampar Regency Education Office. Therefore, public speaking training for prospective trainers is important so that later trainers can deliver learning materials well to students. This community service aims to train public speaking face-to-face in order to improve the rhetorical skills of prospective trainers in the Kampar Regency environment. This community service is carried out using the PAR (Participatory Action Research) method with various stages, namely problem identification, observation followed by training action planning, implementation through the implementation of public speaking training, selection of the best participants, and evaluation at the end of the program. The public speaking skills of prospective trainers improved significantly after the training was conducted. The results of the training show that teachers have global insights, are motivated to improve their abilities to plan to continue their education abroad, and almost all teachers have smoother and more confident public speaking skills. The public speaking training had a positive impact on improving teachers' speaking skills and motivation. Abstrak Pentingnya public speaking dalam dunia pendidikan menjadi hal yang perlu diperhatikan dalam dunia pendidikan di Indonesia, khususnya untuk calon trainer di lingkungan Dinas Pendidikan Kabupaten Kampar. Oleh karena pelatihan public speaking untuk calon trainer menjadi penting dilakukan supaya nantinya trainer dapat menyampaikan materi pembelajaran dengan baik kepada siswa. Pengabdian ini bertujuan untuk melatih public speaking secara tatap muka supaya dapat meningkatkan keterampilan retorika calon trainer di lingkungan Kabupaten Kampar. Pengabdian ini dilakukan dengan metode PAR (Participatory Action Research dengan berbagai tahapan yaitu identifikasi masalah, observasi dilanjutkan dengan perencanaan aksi pelatihan, implementasi melalui pelaksanaan pelatihan public speaking, pemilihan peserta terbaik, dan evaluasi pada akhir program. Keterampilan public speaking calon trainer meningkat secara signifikan setelah pelatihan dilakukan. Hasil pelatiihan menunjukkan bahwa guru memiliki wawasan global, termotivasi untuk meningkatkan kemampuan diri hingga merencanakan melanjutkan pendidikan untuk ke luar negeri, dan hampir seluruh guru memiliki keterampilan public speaking yang lebih smooth dan percaya diri. Pelatihan public speaking berdampak positif bagi peingkatan keterampilan berbicara dan motivasi guru. Kata Kunci: berbicara di depan umum; guru; pelatihan